Genetic Modulation of Transcranial Direct Current Stimulation Effects on Cognition - Wiegand, Ariane; Nieratschker, Vanessa; Plewnia, Christian (Frontiers in Human Neuroscience, 2016)
High inter-individual variability substantially challenges the explanatory power of studies on the modulation of cognitive functions with transcranial direct current stimulation (tDCS). These differences in responsivity have been linked with a critical state-dependency of stimulation effects. In general, genetic diversity is a decisive biological basis of variations in neuronal network functioning. Therefore, it is most likely that inter-individual variability of tDCS-induced changes in cognitive functions is due to specific interactions between genetically determined network properties and the specific type of stimulation. In this context, predominantly the brain-derived neurotrophic factor (BDNF) Val66Met and the catechol-O-methyltransferase (COMT) Val108/158Met polymorphisms have been investigated. The studies on the interaction between the BDNF Val66Met polymorphism and the effect of brain stimulation indicate a critical but yet heterogeneous interaction. But up to now, data on the interplay between this polymorphism and tDCS on cognitive functioning are not available However, recently, the functional Val(108/158)Met polymorphism in the catechol-O-methyltransferase (COMT) gene, that is particularly involved in the regulation of executive functions by means of the dopaminergic tone in frontal brain areas, has been demonstrated to specifically predict the effect of tDCS on cognitive control. Following an inverted U-shaped function, the high dopaminergic activity in Met allele homozygous individuals has been shown to be associated with a reduction of executive functioning by anodal tDCS to the prefrontal cortex. Consistently, Val homozygous individuals with lower dopaminergic tone show a clear reduction of response inhibition with cathodal tDCS. These findings exemplify the notion of a complex but neurophysiologically consistent interaction between genetically determined variations of neuronal activity and tDCS, particularly in the cognitive domain. Consequently, a systematic analysis and consideration of genetic modulators of tDCS effects will be helpful to improve the efficacy of brain stimulation and particularly tDCS in the investigation and treatment of cognitive functions.